Informality, innovation, and firm performance: evidence from World Bank Enterprise Survey in India, 2013–2014 - K. Chandra Shekar (Journal of Innovation and Entrepreneurship)
Abstract This paper re-examines the relationship between informality, innovation and firm performance by analysing firm data from the World Bank Enterprise Survey of India, 2013–2014. We examine whether a firm’s informality, defined by its unregistered status at the time of beginning operations and longer years of being informal, is related to innovation and firm performance while controlling for various firm characteristics and contextual factors. Employing Probit model for innovation outcomes and Tobit model for firm performance and controlling for firm-specific and contextual factors, we find that firms beginning as informal and remaining unregistered for prolonged periods are more likely to introduce new products and processes, leading to superior performance compared to formal counterparts. These findings indicate that weak enforcement of registration laws and the advantages of delayed formalization—such as reduced compliance costs and lower regulatory risks—can incentivize informality. This research underscores the need for industrial and innovation policies that lower entry barriers for informal firms while enhancing the perceived benefits of formality, to foster innovation and inclusive economic growth.